Oral presentation Impact effects of treated wastewaters focusing on present active pharmaceutical ingredients - Vasquez Christodoulou, Marlen (My University, 2026)
Vasquez MI and Fatta-Kassinos D, Impact effects of treated wastewaters focusing on present active pharmaceutical ingredients, Oral presentation, 20th SETAC Europe Annual Meeting, Seville, Spain, 23-27 May 2010.